Immune Response To Stress Induced By Corticosteroid In Common Carp (Cyprinus Carpio Linnaeus) Exposed To Aeromonas Hydrophila - C.Lumanlan, Susan (1993)

(untitled)
The effect of simulated stress induced by cortisol implantation in common carp ( Cyprinus carpio ) was studied. Humoral mediated responses to injected antigens following cortisol treatment were assessed by using the passive haemolytic plaque technique and indirect haemagglutination assay . A single cortisol implant and subsequent challenge to Aeromonas hydrophila elicited modulation in the fish immune system and also histopathological changes in the kidney, spleen and thymus . Hyperglycaemia which is a stress related physiological change was associatively manifested. The marked reduction in haemolytic plaque forming cells in cortisol treated carps indicated the suppression of antibody mediated response ..Similarly , a quantitative decrease in haemagglutinating antibody titre suggested that the immunosuppressive action of cortisol could have a pernicious effect on the fish's ability to resist infection